Antifungal and Physicochemical Properties of Inclusion Complexes Based on β-cyclodextrin and Essential Oil Derivatives - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Mascayano-Collado, C; Galotto-Lopez, M (Elsevier Ltd, 2019)
Inclusion complexes based on β-cyclodextrin (β-CD) and antimicrobial compounds, were prepared by co-precipitation method, and characterized by entrapment efficiency (EE), thermal analysis, X-ray diffraction, 1 H NMR spectroscopy, and water sorption. In addition, experiments associated to evaluate the effect of relative humidity on the release of active compounds and antifungal tests were performed. The analysis evidenced the encapsulation of active compounds into the β-CD structure with EE of 91 ± 4.1% and 66 ± 2.1% for β-CD/cinnamaldehyde and β-CD/eugenol complexes, respectively. Additionally, high relative humidities favored the release of active compounds from inclusion complexes. On the other hand, inclusion complexes were able to control the growth of B. cinerea, which was evidenced by a reduction of its mycelialradial growth. Finally, specific interactions between the active compounds and β-CD were evaluated through molecular dynamics simulation techniques. According to the obtained results, these complexes could be applied as additives in the design of antifungal packaging. © 2019